The Covid-19 pandemic in Sweden: Prolonged and unevenly distributed effects on the volume of pediatric anesthesia and surgery demonstrated by data from the Swedish Perioperative Register - Sixten Melander; Gunnar Enlund; Helene Engstrand Lilja; Peter Frykholm (PLoS ONE, 2025)
Background In 2020, Covid-19 pushed Swedish health care to its limits regarding access to hospital beds and staffing. A previous investigation of the effects of the first wave of the pandemic in the spring of 2020 revealed a substantial reduction in elective pediatric surgery. The aim of the present study was to expand this analysis on a national and regional level during almost three years with Covid-19. Methods For this retrospective cohort study, routine data from all procedures in patients <16 years of age in 2019–2022 were extracted from the Swedish Perioperative Register. Data were analyzed according to level of care, type of surgery, procedure code and emergency or elective surgery. Results During 2020–2022, the number of surgeries registered was 19,944 fewer than expected as compared to pre-pandemic levels, i.e., a reduction of about 12%. Elective surgery showed a total reduction of 17% while emergency surgery was unaffected. The most dramatic decrease was found in county hospitals where elective surgery was reduced by 28% and the largest effect was found in Ear, Nose, and Throat/oral surgery (−34%). Patient age at the time of surgery did not show any notable differences in total, except for grommets insertion in 2021 and adenoidectomy in 2021 and 2022 compared to 2019. Conclusion The Covid-19 pandemic affected the number of surgical procedures in children for more than two years. Future studies of the long-term effects of the large number of canceled operations are warranted.